2018
DOI: 10.31223/osf.io/puz84
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topography and the shallow slip deficit inference

Abstract: Images of earthquake slip serve as the foundation for understanding the distribution of coseismic energy release, theories about rupture propagation, and fault mechanics. Geodetic slip images are inferred using elastic models that link surface observations to fault activity at depth. To date, almost all elastic models used for these common calculations [10, 14, 19, 23] include the assumption that the Earth is flat [1, 6, 11], even for earthquakes in regions of extreme topographic relief like the 2008 MW=7.9 We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This suggests the SSD is overestimated when near‐field data are missing. Finally, setting aside the effect of local topography by using half‐space models may, in some cases, lead to an underestimation of coseismic shallow slip (Thompson & Meade, 2018). Recent studies thus showed that the modeling procedure itself may lead to overestimate shallow slip deficit but were however unable to bring this discrepancy to zero (Marchandon et al, 2018; Xu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the SSD is overestimated when near‐field data are missing. Finally, setting aside the effect of local topography by using half‐space models may, in some cases, lead to an underestimation of coseismic shallow slip (Thompson & Meade, 2018). Recent studies thus showed that the modeling procedure itself may lead to overestimate shallow slip deficit but were however unable to bring this discrepancy to zero (Marchandon et al, 2018; Xu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our inversions account for the uncertainty in geometry and solve for the degree of smoothing where distributed slip is used (sections 3.4 and 4). However, we do not account for any other uncertainties in the forward model, such as errors in elastic structure (Duputel et al, 2014;Ragon et al, 2018) or those introduced by failing to account for topography (Ben Thompson & Meade, 2018;Wang & Fialko, 2018). Inclusion of such model errors would increase the final uncertainties in our results.…”
Section: Methodsmentioning
confidence: 99%